Critical writing in primary school - Gedde-Dahl, Trine; Stavem, Gro Marie; Øgreid, Anne Kristine (Acta Didactica Norden, 2022)
In recent decades, several empirical studies have focused on critical literacy in an educational context. Most of these studies derived their contexts from lower and upper secondary schools and investigated critical literacy as reading, reflection and thinking. In this study, we explore how critical writing may be realized in primary school with the following research question: How are primary school students given the opportunity to develop critical literacy in two writing situations in science classes? Our material is derived from the Norwegian research project Developing national standards for the assessment of writing – a tool for teaching and learning («Normprosjektet», 2012–2016). It consists of two writing tasks about waste sorting and recycling that were responded to in 24 argumentative students’ texts from science classes at two different schools. Field observations are combined with an analytical tool for text analysis using the concepts of topos, domain and discourse to examine how the students engage in three different discourses: the everyday discourse, the science discourse, and the climate discourse. The results show that the students relate to both the everyday discourse and the science discourse, while the climate discourse may play a part and is sometimes explicitly expressed in the student texts. The climate discourse is realized in the texts in slightly different ways at the two schools. We use three perspectives related to critical literacy, subject, discourse conflicts, and positioning, to discuss how writing tasks may provide opportunities for students’ empowerment and development of critical literacy.